2017
DOI: 10.3352/jeehp.2017.14.4
|View full text |Cite
|
Sign up to set email alerts
|

Improving student-perceived benefit of academic advising within education of occupational and physical therapy in the United States: a quality improvement initiative

Abstract: Academic advising is a key role for faculty in the educational process of health professionals; however, the best practice of effective academic advising for occupational and physical therapy students has not been identified in the current literature. The purpose of this quality improvement initiative was to assess and improve the faculty/student advisor/advisee process within occupational and physical therapy programs within a school of allied health professions in the United States in 2015. A quality improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Arenson et al (2015) x x x Ashburner et al (2015) x Baptiste et al (2010) x x x x x Barnes and Parish (2017) x x Bucey and Provident (2018) x x x x x x Copley and Nelson (2012) x Falzarano and Zipp (2012) x…”
Section: Pnmentioning
confidence: 99%
“…Arenson et al (2015) x x x Ashburner et al (2015) x Baptiste et al (2010) x x x x x Barnes and Parish (2017) x x Bucey and Provident (2018) x x x x x x Copley and Nelson (2012) x Falzarano and Zipp (2012) x…”
Section: Pnmentioning
confidence: 99%
“…Twentytwo studies (31%) 27,29,30,32,[39][40][41]48,50,60,70,74,79,81,88,89,96,98,99,101,102,105 used none of these to guide their QI effort. The most commonly cited model/tool was Plan-Do-Study-Act cycles (n 5 19, 27%) 35,38,46,52,54,55,57,58,[63][64][65][66]73,75,78,80,93,100,103 followed by the Model for Improvement (N 5 8, 11%). 38,53,55,57,73,78,80,93 Other organization change models and data demonstration methods common to QI were rarely reported.…”
Section: Qi Models or Toolsmentioning
confidence: 99%
“…Fifty-three studies (76%) reported some form of descriptive statistics, whereas 40 (57%) studies 19,28,[32][33][34][35]37,[39][40][41][43][44][45][46][47][48]50,52,56,59,62,[66][67][68]70,72,74,75,[77][78][79][80][81]89,[95][96][97][100][101][102] reported some type of inferential statistics. Qualitative analysis was used alone in one study (1.8%), 71 but was combined with additional analytic techniques in seven other studies (10%).…”
Section: Analytical Plan Reportedmentioning
confidence: 99%
See 1 more Smart Citation
“…At the core of academic advising effectiveness is the ability to form a positive and consistent relationship with students throughout their matriculation (Barnes & Parish, 2017;Thomas & McFarlane, 2018). In addition, occupational therapy educators may also be required to participate in advising activities that support institutional growth.…”
Section: Teaching and Advisingmentioning
confidence: 99%